Implementasi Pendidikan Akhlak KH. Muhammad Idris Jauhari Dalam Sistem Pendidikan Santri Kelas Akhir Ma’had Tahfidh Al-Qur’an Putri Al-Amien Prenduan - Achmad Maulidi; Fauziatul Mubarokah (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Moral education has an important role in shaping one's behavior. Because in the moral education system is a priority that must be implemented to achieve educational goals. The final grade students at Ma'had Tahfidh Al-Qur'an Putri Al-Amien Prenduan have carried out KH. Muhammad Idris Jauhari, but there are still a handful of students who do not implement it.The focus in this research is:1. How is the concept of moral education KH. Muhammad Idris Jauhari in the Ma'had Tahfidh Al-Qur'an Putri Al-Amien Prenduan Final Grade Santri Education System,2. How is the implementation of moral education KH. Muhammad Idis Juahari in the Ma'had Tahfidh Al-Qur'an Putri Al-Amien Prenduan Final Grade Santri Education System,3. What the supporting and inhibiting factors experienced by students in implementing of moral education KH. Muhammad Idris Jauhari in the Ma'had Tahfidh Al-Qur'an Putri Al-Amien Prenduan Final Grade Santri Education System. This research is a qualitative research. The subjects of this study were caregivers, teachers, and final grade students of Ma'had Tahfidh Al-Qur'an Putri Al-Amien prenduan. And the methods used are interviews, observation, and documentation. Furthermore, the data is presented in an appropriate form so that it is easy to read and understand. Then the data was analyzed and concluded. The results of this study are:1) the concept of moral education KH. Muhammad Idris Jauhari by providing material, giving examples, and applying it in the daily life of students;2) its implementation when visiting (silaturrahmi), speaking, and Ta'zdim;3) the supportive factor is: there is a book of manners, then self-awareness of students, and the teachers who implement the concept of moral education KH. Muhammad Idris Jauhari well. inhibiting factor that is: the different backgrounds of the students, the development of the times and technology, as well as the influence of friends and the prestige of the students.